Enhancement of Service-Oriented Architecture for mobile Internet of Things - Almadhoun, Osama M.M (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Nowadays, Internet of Things (IoT) becomes part and parcel in people's daily life during a growing number of devices with embedding capacities of sensing, actuating, and so on. A significant portion of those devices is mobile devices, which derived with numerous benefits and guide to extraordinary argues. The most meaningful argues, that are directly inherited from today's Internet issues, lie in handling large scale of contributors and mobile devices, supporting interoperability through the heterogeneous devices, and affecting the unidentified vibrant type of the setting. This thesis addresses the challenges of Mobile IoT by enhancing the usually Service-Oriented Architecture (SOA) which permits the operations of embedded sensors in devices to be used as providing services. Despite its capability of SOA, it has not been intended to tackle the extreme -large scale of the mobile IoT. Thus, the main support sits in conceiving architecture that enhance SOA interactions, functionalities, services, and particularly composition component. Three algorithms were developed to improve the composition, expansion, mapping, and execution of Mobile IoT. In addition, the enhancement of novel architecture within Mobile IoT was introduced as architecture resolution that is precisely designed to handle and control the extreme -large number of mobile devices contribute in IoT-related tasks. In order to evaluate the cogency of planned architecture in terms of composition functionality, a prototype implementation of Mobile IoT was conducted based on open source code of CHOReOS project. Eventually, the proposed algorithms have been tested using a number of (between 10 to 1300) parameters (e.g. temperature, wind speed, and windchilled). Results show a good scalability in terms of services and the validity of the code to work with different measurement units or lack of some input parameters. After increasing the number of services by 13 times, the time increased only 28% regardless of the algorithms or equations used in discovery component. Hence it contributes promising results of Mobile IoT and enhances the capabilities of the proposed architecture.